Attitude to the law in Japan Similarities in the constitutions of Uzbekistan and Japan - Zokirov Shohruxbek Zohidjon o‘g‘li (Genius Journals, 2023)
In the article, the attitude towards the law in Japan and the attention paid to legal education in order to build an orderly society in the development of this nation. It is also written about the similarities between the constitutions of Uzbekistan and Japan
Keywords: Uzbekistan; Japan; law; constitution